Implications of Dalalah Amr in Terms the Law of Serving in Covid19 Pandemic Situation - Asmuni Asmuni; Hasan Matsum; Hadi Munawwar (Budapest International Research and Critics University, 2020)
It is an agreement of the ummah, that what Allah revealed in the Al-Qur'an and also what was conveyed by the Messenger of Allah in the Hadith are the basic sources of Islamic law. The two sources, of which there is an order (Amr), this Amr has various meanings such as obligatory, mustahab and others. In this study, the researcher attempted to describe the views of the scholars of jurisprudence in understanding the meaning of amar and its implications for one of the Islamic laws, and here the researcher took one case, namely the practice of worship during the Covid-19 Pandemic. Although most of the Ulama proposing fiqh are of the view that amr basically has a mandatory meaning unless there is a qarinah, in practice there are differences between them. In this study, the researcher used an analytic descriptive method in which after the researcher described the views of the Ulama with regard to the meaning of amr, the designation of the meaning of amar and the legal implications of practicing worship during the Covid-19 Pandemic, considering that at this time there were differences in worship practices that had never happened before Furthermore, the researcher provides some analysis of what the researchers understand based on the views of scholars and experts in this matter.